2010
DOI: 10.1029/2009jc005950
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Mediterranean Sea interannual variability during 1961–2000: Focus on the Eastern Mediterranean Transient

Abstract: This work is dedicated to the study of the climate variability of the Mediterranean Sea, in particular the study of the Eastern Mediterranean Transient (EMT) which occurred in the early 1990s. Simulations of the 1961–2000 period have been carried out with an eddy‐permitting Ocean General Circulation Model of the Mediterranean Sea, driven by realistic interannual high‐resolution air‐sea fluxes. Using different databases for the river runoff, Black Sea inflow, and Atlantic thermohaline characteristics at climato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
228
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(240 citation statements)
references
References 62 publications
(130 reference statements)
9
228
3
Order By: Relevance
“…Data before 1986 -1987 in the EMed exist only from bottle casts at standard depth levels which makes the investigation on the existence of dCIW rather difficult. Nevertheless, several papers [Lascaratos et al, 1999;Theocharis et al, 2002b;Skliris and Lascaratos, 2004;Skliris et al, 2007;Beuvier et al, 2010;Vervatis et al, 2013;Theocharis et al, 2014] based on both observations and numerical modeling have reported a similar event taking place in the eastern part of the EMed during the 1970s. This event was salinity induced and seems to have originated through dense water formation taking place in the Aegean and/or Levantine Seas during a salinity preconditioning phase.…”
Section: Events Of Dciw Outflow and ''Emt-like'' Episodes And Their Rmentioning
confidence: 95%
“…Data before 1986 -1987 in the EMed exist only from bottle casts at standard depth levels which makes the investigation on the existence of dCIW rather difficult. Nevertheless, several papers [Lascaratos et al, 1999;Theocharis et al, 2002b;Skliris and Lascaratos, 2004;Skliris et al, 2007;Beuvier et al, 2010;Vervatis et al, 2013;Theocharis et al, 2014] based on both observations and numerical modeling have reported a similar event taking place in the eastern part of the EMed during the 1970s. This event was salinity induced and seems to have originated through dense water formation taking place in the Aegean and/or Levantine Seas during a salinity preconditioning phase.…”
Section: Events Of Dciw Outflow and ''Emt-like'' Episodes And Their Rmentioning
confidence: 95%
“…It is composed of LMDz4-regional as atmospheric component (Li et al 2012) and of NEMOMED8 (Beuvier et al 2010;Adloff et al 2015) as oceanic component. NEMOMED8 is a regional configuration of the NEMO ocean model (Madec 2008), setup for the Mediterranean Sea.…”
Section: Lmdz-med-fixed Atlanticmentioning
confidence: 99%
“…It has an horizontal resolution ranging from 9 to 12 km and 43 vertical levels. In this simulation, the net "evaporation-precipitation-river" (E-P-R) flux computed over the basin is added in the Atlantic buffer zone, in a way that the volume of the basin is kept constant to a fixed prescribed Atlantic level (Beuvier et al 2010). This model configuration implicitly imposes that basin averaged sea level variations will be very small.…”
Section: Lmdz-med-fixed Atlanticmentioning
confidence: 99%
See 1 more Smart Citation
“…The water exchanges with the Atlantic Ocean are parameterized with a 3D relaxation to this climatology between 11°W and 6°W. The runoffs and the Black Sea water input are prescribed from a climatology as precipitation (Beuvier et al 2010). The vertical diffusion is performed by the standard turbulent kinetic energy model of NEMO and in case of instabilities a higher diffusivity coefficient of 10 m 2 s −1 is used.…”
Section: The Oceanic Modulementioning
confidence: 99%